Ancestor portraits at Mogao Cave 231 - Kyan, Winston (Conversations, 2014)
The integration of “secular” figures into a Buddhist cave complicates the separation established by both medieval Chinese authors and modern scholars of Buddhist art between practices of familial commemoration and religious devotion.